Meta-Analisis Hubungan Antara Kematangan Digital dan Transformasi Digital - Nurul Wahdaniyah; Achmad Nurmandi; Muhammad Younus (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study examines the evolving relationship between digital maturity and digital transformation by conducting a bibliometric analysis. Employing a qualitative literature review supported by VOSviewer, it visualizes keyword co-occurrences and topic clusters. 67 Scopus-indexed publications from 2019 to 2023 were analyzed to uncover research trends and thematic patterns. The findings indicate a substantial rise in scholarly attention to this topic over the past five years. Core concepts such as digital transformation, maturity, technology adoption, and sustainable development emerged as central themes. In contrast, e-government and digital capability remain underexplored, suggesting future research opportunities. Theoretically, this study contributes to a more nuanced understanding of digital maturity, not merely as technological readiness but as a strategic enabler of long-term digital transformation. The study's key contribution is identifying well-developed and under-researched areas and proposing a three-phase digital transformation framework: capability development, strategic alignment, and data-driven sustainable transformation. A key limitation lies in the absence of empirical validation, which underscores the need for future research using primary data and integrating complementary databases.